Drug-induced liver injury: Is chronic liver disease a risk factor and a clinical issue?. (3rd April 2017) - Teschke, Rolf; Danan, Gaby
ABSTRACT: Introduction : Clinicians and practitioners caring for patients with chronic liver disease are often unsure whether drug therapy is a hazard that increases their patient's risk for drug-induced liver injury (DILI). Areas covered : We searched for reports of drug induced liver injury, both idiosyncratic and intrinsic, in patients with chronic liver disease including non-alcoholic and alcoholic liver disease, and cirrhosis. Reports we analyzed include statin treatment in patients with fatty liver, acetaminophen use in alcoholic fatty liver, antituberculous drugs in patients with tuberculosis and viral hepatitis, antiviral medications in hepatitis and antiretroviral medications in HIV/AIDS. The most challenging cases we found are drug therapy in patients with decompensated liver cirrhosis. Expert opinion : We identified many case reports and case series discussing a potential increased risk of DILI in patients with pre-existing liver disease. However, most of these reports were retrospective and ambiguous. With few exceptions, we conclude that drugs seem to be well tolerated by the majority of patients with pre-existing, non-cirrhotic chronic liver diseases. Special care is needed for some therapies, however, including antiviral therapy in chronic hepatitis B and C and in decompensated liver cirrhosis with impaired drug metabolism. Prospective studies are warranted to valid our conclusions.